UNLOCKING THE SECRETS OF VLSs ENGLISH DEPARTMENT STUDENTS AT UNIVERSITAS PGRI SUMATERA BARAT - Yelliza, Yelliza; Siska, Siska (Universitas PGRI Sumatera Barat, 2023)
The objectives of this study were obviously to determine the most and least commonly used vocabulary learning strategies by the students. In addition, it was to identify the reasons behind their use of these strategies. An explanatory mixed-method research design was employed, with the population consisting 3 translation classes in English Department Students at Universitas PGRI Sumatera Barat in the odd semester, academic year 2019/2020. Data was collected through questionnaires and interviews, using the Vocabulary Learning Strategies Questionnaire which contained 40 statements. Descriptive statistics, such as means and standard deviation, were used for statistical analysis. The findings indicated that determination strategies (M=3.32) were the most frequently used vocabulary learning strategies by students, while social consolidation strategies (M=1.82) were the least used. Furthermore, the study explored the reasons behind the students' most and least used strategies. It was found that the students' preferred strategy of using dictionaries to find the meaning of new words was due to its ease and effectiveness, whereas the least used strategy of interacting with native speakers to find new words was limited by the availability of context and vocabulary knowledge.